The effect of task-relevant and task-irrelevant attentional cues and skill level on performance and knee kinematics of standing long jump - Ayoub Asadi; Esmaeel Saemi; Mahmoud Sheikh; Mehdi Takhtaei (Palacký University Olomouc, 2018)
Background: Attention is one of the brain's most crucial cognitive functions playing a key role in performing motor skills. Objective: The purpose of the present study was to investigate the effect of task-relevant and task-irrelevant attentional cues and skill level on performance and knee kinematics of standing long jump. Methods: Fifteen skilled (volleyball and basketball players) and fifteen novices (aged 19 to 27 years) were recruited. The task was the standing long jump test which was executed 9 times under 3 conditions (3 trials per condition). Participants in the control condition did not receive any attentional instruction. In task-relevant attentional cues condition, participants were instructed to focus on their ongoing skill and avoid paying attention to matters unrelated to the task. In task-irrelevant attentional cues condition, participants were instructed to focus on sound and after each jump expressed what had been the musical content. Kinematic data of knee joint was recorded by an 8-camera motion analysis system. Results: The result of mixed ANOVA showed that both novice and skilled groups had significantly greater jump distance and smaller initial knee angle in task-irrelevant attentional cues condition compared to task-relevant attentional cues condition (p = .001) and control condition (p = .001). There were no significant differences between the control and task-relevant attentional cues condition (p > .05). Conclusions: The result showed that focusing attention on task-irrelevant attentional cues improves standing long jump performance of both novice and skilled jumpers.